2004
DOI: 10.1259/dmfr/54013049
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a newly developed dentomaxillofacial X-ray cone beam CT scanner (CB MercuRay™): system configuration and physical properties

Abstract: This study shows that our newly developed cone beam CT system produces high resolution three-dimensional volumetric images that will be useful for the examination of dentomaxillofacial disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
107
0
17

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 169 publications
(129 citation statements)
references
References 15 publications
5
107
0
17
Order By: Relevance
“…A conventional CT scanner acquires sliced-image data with a fan-shaped X-ray beam and rows of detectors. Contiguous cross-sectional images are recon-clinically available 2,3,6,8) . The CBCT scanner can collect volume data by means of a single rotation taking between 9-40 sec due to the use of a cone-shaped X-ray beam and twodimensional detectors.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…A conventional CT scanner acquires sliced-image data with a fan-shaped X-ray beam and rows of detectors. Contiguous cross-sectional images are recon-clinically available 2,3,6,8) . The CBCT scanner can collect volume data by means of a single rotation taking between 9-40 sec due to the use of a cone-shaped X-ray beam and twodimensional detectors.…”
Section: Introductionmentioning
confidence: 99%
“…This means that CBCT scanners have the potential to offer additional benefits in hard-tissue visualization of the maxillofacial region and evaluation of skeletal morphology. Earlier studies 2,3,6,8) have shown that CBCT offers great advantages in comparison with conventional CT in depiction of the maxillofacial region, in terms of accuracy, scan time reduction, dose reduction, and convertible field of view (FOV), and so on. However, at the moment such systems also suffer from the disadvantages of being relatively expensive and unreliable in demonstrating soft tissue abnormalities.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations